Examining The Role of HR Management in Enhancing Remote‎Employee Satisfaction: Critical Influencing Factors - Verma, Manish Kumar; Sinha, Dr Ashish Ranjan; Kaushal, Shrutikeerti (International Journal of Accounting and Economics Studies, 2025)
Employee satisfaction is crucial for organizational success, influencing productivity, as well as retention morale. The IT sector's shift to‎wards remote work, driven by technological advancements, has altered traditional work dynamics. Remote work offers flexibility but also ‎poses challenges to employee satisfaction. To address these, human resource management (HRM) development practices must evolve. By ‎identifying and prioritizing key factors, the research provides insights for optimize HRM practices to enhance the remote work environ‎ment. Sampling done through stratified random sampling, A questionnaire on the Likert scale was distributed to IT workers from Indian businesses. The ‎t-test and structural equation modeling (SEM) were utilized for inferential and illustrative insights in the information analysis. HRM practic‎es and employee satisfaction were found to have a significant positive correlation, according to the study. One of the most important find‎ings is that counseling, career development, teamwork spirit, and training and development all have a significant impact on employee satis‎faction and career growth. Career development and counseling had a negative impact on employee satisfaction, whereas teamwork, training, ‎and development have a positive impact on employee performance. The findings emphasize the significance of individualized HRM practic‎es for increasing remote employee satisfaction. Organizations can improve overall performance and employee well-being by recognizing and ‎meeting the specific needs of remote workers. Understanding the crucial role of Remote employees this is the first work that aims to understand the factors that promote satisfaction of these employees with particular reference to IT sector in India. Although there have been stud‎ies conducted on IT sector employees but none of the studies have been conducted on those employees that work remotely‎.